Emergence of Clostridium difficile NAP1 in Latin America - Quesada Gómez, Carlos (2010)
The NAP1 and NAP2 strains of Clostridium difficile have been linked to nosocomial outbreaks of antibiotic-associated diarrhea (AAD) and pseudomembranous colitis in North American and European countries (4, 5). We found these strains, together with seven additional pulsed-field gel electrophoresis (PFGE) patterns, among 37 isolates recently recovered from patients with AAD in a Costa Rican hospital. Herein we present the macrorestriction patterns of the isolates as well as data regarding their toxin genotypes and susceptibility to selected antibiotics.